1990
DOI: 10.1021/ma00221a005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and carbon-13 nuclear magnetic resonance investigation of the intramolecular structure of solution and emulsion styrene-methyl acrylate copolymers

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…7 The intramolecular structure of styrenemethacrylate (STY-MA) copolymers was evaluated by 1 H-and 13 C-NMR studies and also by 2D-NMR COLOC experiments. 8 The use of phenyl (meth)acrylates as weather-resistant, highglass top coats for automobile finishes has been reported. 9 Poly(phenyl methacylates) are harder polymers of higher tensile strength and lower elongation than their acrylate counterparts because substitution of the methyl group for the ␣-H on the main chain restricts the freedom of rotation and motion of the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…7 The intramolecular structure of styrenemethacrylate (STY-MA) copolymers was evaluated by 1 H-and 13 C-NMR studies and also by 2D-NMR COLOC experiments. 8 The use of phenyl (meth)acrylates as weather-resistant, highglass top coats for automobile finishes has been reported. 9 Poly(phenyl methacylates) are harder polymers of higher tensile strength and lower elongation than their acrylate counterparts because substitution of the methyl group for the ␣-H on the main chain restricts the freedom of rotation and motion of the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Van Doremaelae et a/. 9 have reported a similar type of assignment for styrene/methyl acrylate copolymers. Concentration of various A-centered triads can be calculated from the relative areas of respective signals.…”
Section: Resultsmentioning
confidence: 71%
“…Hence it is of interest to examine the microstructure and statistics of this copolymerization using 13 C NMR spectroscopy. Although a variety of copolymers of acrylamide ( acrylamide-acrylic acid), 4 -7 trimellictic anhydride-co-imides, 8 and styrene (styrene-methacrylate, 9 styrene-methacrylonitrile 10 ) has been studied by 13 C NMR spectroscopy, there is no report in the literature on poly( styrene-co-aery !amide )s.…”
mentioning
confidence: 99%
“…The spatial coupling between the methylene dyads SS and MS with the phenylic protons was observed and it was assigned to SSrSS (7), SSrSM (8), and MSrSM (9) tetrads for the coupling with SS at ␦1.4/6.88, ␦1.45/7.1, and ␦1.58/7.15 ppm, respectively. The SMmSS (10), SMmSM (11), and MMmSM (12) tetrads for the spatial coupling of the MS dyad with styrene protons at ␦1.6/6.92, ␦1.85/7.2, and ␦1.9/6.8 ppm were assigned. The dyad MM cannot have any crosspeak with phenylic protons, that is, it is evident from the NOESY spectra.…”
Section: D-nmr Studiesmentioning
confidence: 99%
“…2D-heteronuclear NMR spectroscopy is being frequently used for the study of homopolymers 6 -9 and copolymers. 10 Van Doremaele et al 11 reported the intermolecular structure (triad distribution, tacticity parameter) of methyl acrylate-styrene copolymers using 1 H and 13 C experiments. Koinuma et al 12,13 interpreted the 13 C-NMR spectra of a methyl acrylatestyrene copolymer using a theoretical model.…”
Section: Introductionmentioning
confidence: 99%